Aktivitas Antifungi Ekstrak Etanol Daun Salam (Syzygium polyanthum (Wight) Walp.) terhadap Pertumbuhan Jamur Candida albicans secara in vitro - Any Fitriani; Yanti Hamdiyati; Ria Engriyani Ria Engriyani (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2012)
Antifungal activity of the ethanol extract of bay-leaf (Syzygium  polyanthum (Wight) Walp.) against growth of the fungus Candida albicans in vitro has been conducted. Leaves of S. polyanthum has been known to have potential as antifungal for skin fungal pathogen. This study aims to determine antifungal activity of the ethanol extract of S. polyanthum leaves against growth of C. albicans.  Activity test was done by disc-diffusion  method and macro-dilution. This study used concentrations of ethanol leaf extract of S. polyanthum of 0.5%, 1%, 1.5%, 2%, and 2.5% (w/v). Negative control using 1% DMSO and positive controls using ketoconazole 30 mg/mL. The results shows that ethanol extract of leaves of S. polyanthum have activity as an antifungal. Ethanol extract of leaves of S. polyanthum based on the results of GCMS analysis of compounds containing chemical compounds such as terpenoids and fatty acids. Ethanol extract of leaves of S. polyanthum showed the highest inhibition zone diameter at a concentration of 1% (w/v) of 9.32 ± 0.21 mm. Value of Minimum inhibitory Concentration (MIC) for ethanol leaf extract of S. polyanthum present in a concentration of 0.5% (w/v) and the value of Minimum Fungicidal Concentration (MFC) present in a concentration of 1% (w/v).